Научно-теоретические проблемы медицины транспорта - Шафран, Л.М. (Актуальні проблеми транспортної медицини, 2005)
Definition of the term “medicine of transport” is made as applied medical scientific discipline and sphere of practical activities on the safety, health preservation and sanitary-and-epidemiologic wellbeing of workers, population and the environment protection in a context of steady development of all types of transport. Five basic directions of medicine of transport, their purpose and main tasks are considered. It is shown, that in the scientific-theoretical researches of the mentioned scientific discipline the problem of adaptation is the basic one. Its development has fundamental values for the medicine of transport and both workers and population health management.